STRATEGI PEMASARAN DIGITAL PENINGKATAN PENJUALAN BATIK DI MASA PANDEMI COVID 19 - Pratiwi, Adcharina (JURNAL GAUNG INFORMATIKA, 2022)
The research was carried out at batik Busana Asri, the Pilang Batik Industry Center, Masaran, Sragen. This study aims to formulate a digital-based marketing implementation strategy to increase batik sales volume. The benefits of research are generated by formulating models and implementing batik marketing in the new normal period of the COVID-19 pandemic. The object of this research is Batik Clothing Asri at the Pilang Masaran Batik Industry Center, Sragen. Data collection methods are through questionnaires, observations, interviews and direct activities at Batik Busana Asri. The analytical method designed the concept of a digital marketing implementation model and through regression to determine the effect of the digitalization marketing strategy implementation indicators on sales volume. Marketing digitization strategy variables include: company web site (X1), tiktok social media (X2), Instagram social media (X3), facebook social media (X4), digital marketing (shopee) X5, product catalog (X6), youtube social media (X7), company signage promotion (X8) and sales volume (Y). Based on the resulting analysis: (1) the formulation of a digital-based marketing implementation model, (2) digital marketing (shopee) dominantly affects the increase in sales volume, (3) the overall implementation of digitalization variables affects the increase in sales volume. The marketing strategy model for the implementation of marketing digitalization is able to increase the volume of batik sales in the UKM Batik Busana Asri, the Pilang Masaran Batik Industry Center, Sragen